2006
DOI: 10.1016/j.febslet.2006.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Hcc‐2, a novel mammalian ER thioredoxin that is differentially expressed in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the most common primary cancer of the liver. Thus there is great interest to identify novel HCC diagnostic markers for early detection of the disease and tumour specific associated proteins as potential therapeutic targets in the treatment of HCC. Currently, we are screening for early biomarkers as well as studying the development of HCC by identifying the differentially expressed proteins of HCC tissues during different stages of disease progression. We have isolated, by reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Wang et al (2007) has suggested that an upregulation of TXNDC5 could be involved in the early development of colorectal cancer by proteomic analysis of differentially expressed proteins in adenoma, when compared with matched normal mucosa and cancer tissue. Nissom et al (2006) has found that the TXNDC5 expression is upregulated in poorly differentiated hepatic carcinoma (HCC), but unchanged in well-differentiated HCC and thought the gene could play some roles in tumor progression. Claudio et al (2002) has found that TXNDC5 is upregulated in multiple myeloma and Wei et al (2007) showed that TXNDC5 is upregulated in androgen-independent prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (2007) has suggested that an upregulation of TXNDC5 could be involved in the early development of colorectal cancer by proteomic analysis of differentially expressed proteins in adenoma, when compared with matched normal mucosa and cancer tissue. Nissom et al (2006) has found that the TXNDC5 expression is upregulated in poorly differentiated hepatic carcinoma (HCC), but unchanged in well-differentiated HCC and thought the gene could play some roles in tumor progression. Claudio et al (2002) has found that TXNDC5 is upregulated in multiple myeloma and Wei et al (2007) showed that TXNDC5 is upregulated in androgen-independent prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…α-enolase was strongly expressed in G3 tumours compared with G1 and G2 tumours (12), and glutamine synthetase was highly expressed in HCV-infected G1 tumours (15). Recently, protein Hcc-2 was found to be upregulated in G3 tumours but unchanged in G1 tumours (16). In addition, proteome profiles of HCC are also virus-dependent.…”
Section: Introductionmentioning
confidence: 86%
“…This novel protein was identified by proteomic analysis and was designated as Hcc-2, which is up-regulated in poor-differentiated HCC but unchanged in well-differentiated HCC. This work demonstrated that an integrated proteomic and genomic approach could be a very powerful means of discovering potential diagnostic and therapeutic protein targets for cancer therapy [51]. …”
Section: Biomarkers For Targets In Cancer Therapymentioning
confidence: 99%